IMPACT OF ADOPTION OF FINANCIAL STANDARDS AND INNOVATIONS ON SME BUSINESS PERFORMANCE: THE ROLE OF COMPETITIVE ADVANTAGE AS A MEDIATION - Inrawan, Ady; Silitonga, Hery Pandapotan; Halim, Fitria; Sudirman, Acai; Lie, Darwin (Jurnal Ilmu Keuangan dan Perbankan (JIKA), 2021)
This study aims to determine the role of competitive advantage in mediating the relationship between the adoption of financial reporting standards and innovation on the business performance of SMEs in Pematangsiantar City. This study uses a research design with a quantitative approach to causality. Data collection techniques using observation, interviews, questionnaires and documentation. The sampling method used in this study is the convenience sampling method. The data analysis method used is Partial Least Square (PLS).The data analysis test tool uses the statistical software Smartpls 3.0. The results showed that innovation and competitive advantage had a significant effect on business performance, the adoption of financial reporting standards on business performance obtained an insignificant impact. Whereasthe effect of the adoption of financial reporting standards on competitive advantage obtained significant results. Furthermore, the effect of innovation on competitive advantage obtained insignificant results. Then competitive advantage can mediate the relationship between the adoption of financial reporting standards on business performance. Furthermore, the competitive advantage variable is not able to mediate the relationship between innovation and business performance.